Pengenalan Aplikasi Canva Sebagai Desain Media Pembelajaran Otomatis Bagi Guru di SMAS Plus Talang - Dewilna Helmi; Dwi Partini; Asep Asep; C. S. A Barus (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The rapid development of technology has reached the era 5.0 where digital literacy has become extremely important, especially for teachers. One of the graphic design applications that can assist teachers in designing instructional media is Canva. The purpose of this community engagement activity is to introduce the Canva application to teachers at SMAS Plus Talang as a tool for designing instructional media. The methods used in this engagement include lectures, practice sessions, and discussions. There are several stages in this engagement activity, namely coordination and needs analysis, preparation of materials and activities, training, monitoring and evaluation, as well as data analysis and reporting. The results of this engagement show an improvement in the understanding of the teachers after participating in the training, with an average understanding categorized as very good. This Community Engagement (PKM) activity helps teachers in designing engaging instructional media, enabling students to become more aware of digital literacy and be prepared to face a digital-dominant work environment. It is hoped that the results of this research can serve as a reference for other educational institutions and introduce and train educators in the use of the Canva application.